2010
DOI: 10.1111/j.1540-8167.2010.01756.x
|View full text |Cite
|
Sign up to set email alerts
|

Isolated Potentials and Pace‐Mapping as Guides for Ablation of Ventricular Tachycardia in Various Types of Nonischemic Cardiomyopathy

Abstract: IPs in conjunction with pace-mapping are helpful for identifying critical isthmus areas for ablation of VT in patients with various types of nonischemic cardiomyopathy. Patients with nonischemic cardiomyopathy in whom the arrhythmogenic substrate is characterized by IPs have a more favorable outcome than patients in whom IPs are absent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(16 citation statements)
references
References 17 publications
0
16
0
Order By: Relevance
“…Ouyang et al 24 described the presence of LPs at the epicardial mapping in 4 patients with exercise‐induced VTs in the context of inferolateral aneurysm and normal endocardial substrate. Kuhne et al 25 demonstrated that in patients with nonischemic cardiomyopathy presence of LPs predicted a better outcome after the ablation. Those results were confirmed by Nakahara et al , 11 who proved a more favorable prognosis in patients with an higher density of very LPs.…”
Section: Discussionmentioning
confidence: 99%
“…Ouyang et al 24 described the presence of LPs at the epicardial mapping in 4 patients with exercise‐induced VTs in the context of inferolateral aneurysm and normal endocardial substrate. Kuhne et al 25 demonstrated that in patients with nonischemic cardiomyopathy presence of LPs predicted a better outcome after the ablation. Those results were confirmed by Nakahara et al , 11 who proved a more favorable prognosis in patients with an higher density of very LPs.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, an ablation strategy targeting LPs was highly successful in the ICM patients (82% freedom from VT at 12 month followup) yet the NICM cohort only had a 50% freedom from VT at 15 months 13 . Consistent with these observations, Kuhne et al 14 also assessed the prevalence of late potentials in patients with NICM undergoing VT ablation and noted a marked improvement in outcomes (67% vs 7% freedom from VT) in patients with late potentials identified versus those without. The differences in late potential characterization seen between the ICM and NICM groups once again highlight the differences in scar biology in patients with NICM and reinforce the notion that current ablation strategies remain suboptimal.…”
Section: Location Of the Arrhythmogenic Substratementioning
confidence: 70%
“…31,32 Of note, mapping of abnormal EGMs during RV pacing may be more sensitive than during normal sinus rhythm (NSR) or biventricular pacing due to a change in the direction of the activation wave front (see Figure 1). 33 Following substrate characterisation, VT induction is attempted ( Figure 2).…”
Section: Substrate Characterisationmentioning
confidence: 99%